Acoustic Properties of Low Density Oil Palm (Elaeis Guineensis Jacq) Fibreboard - Bokhari, Semsolbahri (2000)
An ultrasonic test was carried out to determine the acoustic properties of low density oil palm fibreboard. The main objective of this study was to investigate the suitability of using oil palm empty fruit bunches (EFB) as partial replacement for the acoustic materials in audio room. The board was manufactured by using rubberwood (Hevea bracilliensis) and oil palm (Elaeis guineensis, Jacq). The rubberwood was used as the control. Three levels of board density and five thicknesses were used to investigate the relationship of acoustic parameters (wave velocity and attenuation coefficient) to these independent variables. In addition, this study consisted of two sub-studies; (i) the effect of resin content on the acoustic properties, and (ii) the trend of pulse velocity travelling through the boards of different thicknesses. The result showed that the acoustic properties of oil palm boards were significantly affected by a variation in board densities and thicknesses, as well as resin content. On the other hand, it was found that the velocity of pulse was influenced by the variation in the resin content, thickness and density of the boards. The pulse velocity, which travels through the EFB, was similar to that of rubberwood boards, suggesting that the acoustic properties of EFB were in the same class as that of rubberwood. The board with 12 mm thickness was found to be able to absorb more pulse wave than the board of other thicknesses for each type of board density. Based on the result, the low density oil palm fibreboard was suitable to be used as a core layer for building a wall in audio room. However, it needs further improvement on it's design and structure to have a better performance as the absorbent materials. This study also found that the ultrasonic test could be a good non-destructive test method to assess the acoustic properties.